Lithium-rich manganese-based positive electrode material surface coating layer and preparation method thereof

By using atomic layer deposition technology to form a cladding layer on the surface of lithium-rich manganese-based positive electrode material and forming a doped layer in combination with gradient heat treatment, the voltage attenuation and cyclic stability of the material in terms of high energy density and long life is solved, and the rate performance and stability of the battery are significantly improved.

CN119742340AActive Publication Date: 2025-04-01CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411930361.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have problems of voltage attenuation, cycle stability and poor rate performance in terms of high energy density and long life, especially the interface side reactions with solid electrolytes under high operating voltages.

Method used

Atomic layer deposition technology is used to form a cladding layer on the surface of lithium-rich positive electrode material, and a doped layer is formed through gradient heat treatment to form a cladding and micro-doped structure to improve the electrochemical performance of the material.

Benefits of technology

The cycle stability and high voltage stability of lithium-rich manganese-based positive electrode materials are significantly improved, voltage attenuation and interface side reactions are suppressed, and the rate performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742340A_ABST
    Figure CN119742340A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a surface coating layer of a lithium-rich manganese-based positive electrode material, which comprises the following steps: S1, introducing a precursor A into the surface of a lithium-rich positive electrode material for reaction by adopting an atomic stratification method, then introducing a precursor B for reaction, and repeating the previous introduction process to obtain a coating layer semi-finished product with required thickness; and S2, gradient heating: heating the semi-finished product of the surface coating layer of the lithium-rich manganese-based positive electrode material in a manner of keeping the temperature for 10 hours at each gradient temperature at the gradient of 400-500-600 DEG C until a doping layer with a transition structure is formed between the coating layer and the lithium-rich positive electrode material, the doping layer is Li [gamma] TiaOb, a2 is more than or equal to 0 and less than or equal to 5, b2 is more than or equal to 0 and less than or equal to 5, gamma is more than or equal to 0.1 and less than or equal to 5, and finally, the surface-coated and micro-doped lithium-rich positive electrode material is obtained. According to the method, the lithium-rich manganese-based positive electrode material has excellent cycling stability and can remarkably inhibit voltage attenuation, and the preparation method is simple, low in cost, good in repeatability and capable of achieving large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery coating, and in particular to a surface coating layer of a lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles, energy storage systems and other fields, the requirements for lithium battery energy density are constantly increasing. The clear goal of battery pack technology: by 2025 and 2030, it is expected to achieve a battery energy density of 400Wh / kg and 500Wh / kg respectively. The United States Advanced Battery Consortium (USABC) also emphasized the importance of battery energy density, pointing out that in order to improve the driving range of pure electric vehicles, the battery energy density should reach 350Wh / kg, and the system-level battery energy density should reach 250Wh / kg. Lithium-ion batteries are widely used in the electric vehicle market due to their outstanding advantages in performance and cost. However, the growth rate of the energy density of liquid lithium-ion batteries is gradually slowing down and approaching its theoretical limit. The current mainstream energy density of lithium iron phosphate batteries is less than 200Wh / kg, while the energy density of ternary lithium batteries is 200-300Wh / kg, which still cannot meet the needs of some electric vehicles and large-scale energy storage. In view of this, continuing to make innovative breakthroughs in existing battery materials and battery systems, breaking the shackles of material technology, and developing all-solid-state battery technology with higher energy density are the key to the development of lithium-ion batteries.

[0003] Lithium-rich manganese-based cathode materials are widely used to build high-energy-density all-solid-state batteries to solve the "mileage anxiety" problem in the current new energy vehicle field due to their ultra-high specific capacity (300mAh / g) and extremely high energy density (1000Wh / kg). However, the voltage decay, cycle stability and poor rate performance of the material itself have severely restricted its further application. At the same time, the serious interfacial side reactions between lithium-rich and solid electrolytes at high working voltages (>4.5V) further aggravate the capacity decay. In view of this, many improvement strategies such as surface coating, element doping, and structural gradient design have been developed. Among them, surface coating modification is widely used because of its easy operation, low cost, and good effect. It is worth noting that traditional coating methods such as liquid phase method and solid phase method are difficult to form a uniform, dense and multifunctional coating layer. At the same time, a single treatment process cannot effectively solve the current systemic problems of the material itself and the electrolyte interface. Therefore, an in-situ system integration method is needed to construct a surface coating layer of lithium-rich manganese-based positive electrode materials with high specific energy and high stability to construct a composite functional coating layer to achieve high-energy and long-life lithium-rich manganese-based all-solid-state batteries.

[0004] Atomic layer deposition (ALD) technology is a method of chemical vapor deposition of thin films based on ordered, surface self-limiting reactions. It is a method of forming a thin film by alternately pulsed gas-phase precursors into the reaction chamber and causing gas-solid chemical adsorption reactions on the surface of the deposition substrate. Its advantages such as precise controllable reactions, precise controllable thickness at the atomic layer level, and self-limited reactions have attracted widespread attention. Unfortunately, the current mainstream ALD coatings are mostly metal oxides, which have low ion conductivity, severely restricting interfacial ion transport, and thus affecting battery rate performance. Secondly, the incompatibility of the coating and the substrate also increases the interface resistance. Summary of the invention

[0005] In order to solve the above problems, the purpose of the present invention is to provide a surface coating layer of a lithium-rich manganese-based positive electrode material and a preparation method thereof, which enables the lithium-rich manganese-based positive electrode material to have extremely excellent cycle stability while significantly inhibiting voltage decay. The preparation method is simple, low-cost, and has good repeatability and can be mass-produced.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a surface coating layer of a lithium-rich manganese-based positive electrode material comprises the following steps: S1, obtaining a surface coating layer of a lithium-rich manganese-based positive electrode material: using an atomic layer deposition method, first introducing a precursor A to react, then introducing a precursor B to react, repeating the previous introduction process, and obtaining a semi-finished coating layer of a required thickness, wherein the precursor A is a titanium compound, including one of tetrakisdimethylaminotitanium TDMAT or titanium tetrachloride TiCl4; the precursor B provides an oxidizing substance for the coating layer, and the coating layer is a binary oxide of titanium, Ti a1 O b1 , where 0≤a1≤5, 1≤b1≤6; S2, gradient heating: heating the semi-finished product of the coating layer on the surface of the lithium-rich manganese-based positive electrode material at a gradient of 400℃-500℃-600℃, with each gradient temperature being kept for 10 hours, until a doping layer of a transition structure is formed between the coating layer and the lithium-rich positive electrode material, and the doping layer is Li γ Ti a O b , where 0≤a2≤5, 0≤b2≤5, 0.1≤γ≤5, and finally a surface-coated and slightly-doped lithium-rich positive electrode material is obtained.

[0008] Precursor A is introduced into S1 and the reaction is maintained for 1-120s. Precursor B is introduced into S1 and the reaction is maintained for 1-120s. Inert gas is introduced after the precursors are introduced into the reaction. The gradient heating in S2 is specifically as follows: the surface coating layer of the lithium-rich manganese-based positive electrode material obtained in S1 is heated to 400°C at a heating rate of 5°C / min and kept warm for 10h; after the insulation is completed, the temperature is then increased to 500°C at a heating rate of 5°C / min and kept warm for 10h; after the insulation is completed, the temperature is then increased to 600°C at a heating rate of 5°C / min and kept warm for 10h.

[0009] Li-rich cathode materials include Li 1+x Ni y Co z Mn t M s O2, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤t≤1, 0≤s≤1, and M includes one of Al, Ti or Mo.

[0010] A method for preparing a coating layer on the surface of a lithium-rich manganese-based positive electrode material to obtain a coating layer, firstly, by an atomic deposition method, a precursor A and a precursor B are sequentially introduced into the surface of the lithium-rich manganese-based positive electrode material, and the deposition is cyclically performed until a coating layer semi-finished product of a desired thickness is obtained, and then the coating layer semi-finished product obtained in the previous step is subjected to gradient heating until a doping layer of a transition structure is formed between the coating layer semi-finished product and the lithium-rich positive electrode material to obtain a finished product, wherein the doping layer is Li γ Ti a2 O b2 , where 0≤a2≤5, 0≤b2≤5, 0.1≤γ≤5.

[0011] As mentioned above, the coating layer has a thickness of 0.1-20 nm.

[0012] The inventors found that the gradient heat treatment process can effectively improve the performance of the ALD coating, and the synergistic treatment of the two can effectively solve the interface problems currently faced by solid-state batteries. The present invention effectively improves the high voltage stability and battery rate performance through the synergistic effect of atomic layer deposition technology and gradient heat treatment process, and inhibits voltage decay and interface side reactions.

[0013] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0014] The present invention coats a metal oxide layer with a thickness of 0.1-10nm on the surface of the lithium-rich positive electrode, and forms a precisely controllable element doping through subsequent gradient heat treatment, and forms a fast ion conductor micro-doping layer on the surface, and the two work together to significantly improve the battery performance. This method enables the lithium-rich manganese-based positive electrode material to have extremely excellent cycle stability while significantly suppressing voltage decay, and the preparation method is simple, low-cost, and has good repeatability, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0016] Figure 1 It is a schematic diagram of the structure of lithium-rich positive electrode material after coating and doping.

[0017] Figure 2 It is an X-ray diffraction diagram corresponding to the material shown in Example 1 of the present invention.

[0018] Figure 3 It is a transmission electron microscope image corresponding to the material shown in Example 1 of the present invention.

[0019] Figure 4 It is a cycle curve diagram of the uncoated initial sample of the material shown in Example 1 of the present invention at an operating voltage of 2.5-4.8V.

[0020] Figure 5 It is a cycle curve diagram corresponding to the material coated sample shown in Example 1 of the present invention at an operating voltage of 2.5-4.8V.

[0021] Figure 6 It is a first cycle charge and discharge curve diagram of the material shown in Example 1 of the present invention and the corresponding comparative example at an operating voltage of 2.5-4.8V. DETAILED DESCRIPTION

[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0023] Example 1

[0024] Construct a titanium oxide layer on the surface of the lithium-rich positive electrode. (1) Weigh 15g of lithium-rich positive electrode material, place it in a vacuum oven, and vacuum dry it at 80°C for 6 hours to remove the water adsorbed on the surface. (2) Place the dried lithium-rich positive electrode material into an atomic layer deposition reaction bottle, place the reaction bottle into the reaction chamber, and evacuate it to below 0.1mPa. (3) Raise the temperature to 260°C in the reaction chamber and 85°C in the pipeline. Keep the precursor tetradimethylamine titanium (TDMAT) and water at room temperature. (4) Turn on the rotary switch to heat the reaction bottle evenly. When the temperature reaches the set value, use nitrogen as the carrier gas, open the TDMAT valve for 1 second, and introduce tetrakisdimethylaminotitanium TDMAT into the reaction chamber. After reacting for 30 seconds, introduce nitrogen to purge for 90 seconds to remove the unreacted precursor from the reaction chamber; (5) Open the water valve for 1 second, and introduce water into the reaction chamber. After reacting for 60 seconds, introduce nitrogen to purge for 90 seconds to remove the unreacted water and reaction by-products from the reaction chamber. (2)-(4) is a complete cycle. Repeat the above steps 5 times to obtain a coating layer with a thickness of about 1 nm, with a structure as shown in FIG. Figure 1 shown.

[0025] The above materials were placed in a muffle furnace, and the surface coating layer of the lithium-rich manganese-based positive electrode material obtained in S1 was heated to 400°C at a heating rate of 5°C / min and kept warm for 10 hours; after the insulation was completed, the temperature was then increased to 500°C at a heating rate of 5°C / min and kept warm for 10 hours; after the insulation was completed, the temperature was then increased to 600°C at a heating rate of 5°C / min and kept warm for 10 hours to obtain a surface-coated and slightly doped positive electrode material, forming a lithium aluminate doping layer. The XRD and TEM images after ALD coating and doping are shown as follows: Figure 2 , as shown in 3.

[0026] The above two materials are mixed and ground with conductive carbon black and halide solid electrolyte to obtain a positive electrode for solid-state batteries. The above positive electrode is assembled into an all-solid-state battery in a glove box filled with argon, in which a metal lithium-indium alloy is used as the negative electrode, and a halide solid electrolyte and a sulfide solid electrolyte double layer are used as the electrolyte. The assembled all-solid-state battery is taken out of the glove box for subsequent electrochemical performance testing. The cycle curve at a current density of 200mAh / g is shown in FIG. Figure 4 , as shown in Figure 5. The electrochemical performance shows that the cycle stability of the treated lithium-rich cathode is greatly enhanced, indicating the great application prospects of the present invention.

[0027] Example 2

[0028] Similar to Example 1, the difference is that another precursor titanium tetrachloride TiCl4 is used for coating and gradient heating treatment is performed.

[0029] Comparative Example 1

[0030] Similar to Example 1, the difference is that coating is performed but no gradient heating treatment is performed, that is, the heating and heat preservation is always carried out at a temperature of 400° C., and other conditions are the same.

[0031] Comparative Example 2

[0032] Similar to Example 1, the difference is that no coating is performed, but gradient heating treatment is performed.

[0033] from Figure 4 , 5 It can be clearly seen that the cycle stability of the embodiment is significantly enhanced, far superior to the comparative example. Figure 6 It can be seen that the first cycle reversible capacity of comparative examples 1 and 2 is less than 230 mAh / g, which is far less than the reversible capacity of examples 1 and 2> 250 mAh / g. In summary, the technology of the present invention has outstanding gains in the cycle stability and reversible capacity of lithium-rich manganese-based positive electrode materials, and has very good application prospects.

[0034] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a surface coating layer of a lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: S1. Obtaining a coating layer on the surface of a lithium-rich manganese-based positive electrode material: using an atomic layer deposition method, first introducing a precursor A to react, then introducing a precursor B to react, repeating the previous introduction process, and obtaining a coating layer semi-finished product of a required thickness, wherein the precursor A is a titanium compound, including one of tetrakisdimethylaminotitanium TDMAT or titanium tetrachloride TiCl4; the precursor B provides an oxidizing substance for the coating layer, and the coating layer is a binary oxide of titanium, Ti a1 O b1 , where 0≤a1≤5, 1≤b1≤6; S2, gradient heating: heating the semi-finished product of the coating layer on the surface of the lithium-rich manganese-based positive electrode material at a gradient of 400℃-500℃-600℃, with each gradient temperature being kept for 10 hours, until a doping layer of a transition structure is formed between the coating layer and the lithium-rich positive electrode material, and the doping layer is Li γ Ti a O b , where 0≤a2≤5, 0≤b2≤5, 0.1≤γ≤5, and finally a surface-coated and slightly-doped lithium-rich positive electrode material is obtained.

2. The preparation method according to claim 1, characterized in that: Precursor A is introduced into S1 and the reaction is maintained for 1-120 seconds.

3. The preparation method according to claim 1, characterized in that: Precursor B is introduced into S1 and the reaction is maintained for 1-120 seconds.

4. The preparation method according to claim 1, characterized in that: After the precursor is introduced into the reaction, an inert gas is introduced.

5. The preparation method according to claim 1, characterized in that: The gradient heating in S2 is specifically as follows: the surface coating layer of the lithium-rich manganese-based positive electrode material obtained in S1 is heated to 400°C at a heating rate of 5°C / min and kept warm for 10 hours; after the insulation is completed, the temperature is then heated to 500°C at a heating rate of 5°C / min and kept warm for 10 hours; after the insulation is completed, the temperature is then heated to 600°C at a heating rate of 5°C / min and kept warm for 10 hours.

6. The preparation method according to claim 1, characterized in that: Li-rich cathode materials include Li 1+x Ni y Co z Mn t M s O2, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤t≤1, 0≤s≤1, and M includes one of Al, Ti or Mo.

7. The preparation method according to claim 1, characterized in that: The coating thickness of the semi-finished coating layer is 0.1-10 nm.

8. A method for preparing a coating layer on the surface of a lithium-rich manganese-based positive electrode material. The coating layer is firstly introduced into the surface of the lithium-rich manganese-based positive electrode material by an atomic deposition method in sequence, and the precursor A and the precursor B are cyclically deposited until a coating layer semi-finished product of a desired thickness is obtained, and then the coating layer semi-finished product obtained in the previous step is subjected to gradient heating until a doping layer of a transition structure is formed between the coating layer semi-finished product and the lithium-rich positive electrode material to obtain a finished product, wherein the doping layer is Li γ Ti a2 O b2 , where 0≤a2≤5, 0≤b2≤5, 0.1≤γ≤5.

9. The coating layer according to claim 7, having a thickness of 0.1-20 nm.

Citation Information

Patent Citations

  • Method for constructing double coating layers on surface of lithium-rich positive electrode material through atomic layer deposition

    CN114613993A

  • Lithium-rich manganese-based positive electrode material with surface gradient doping type composite structure and preparation method of lithium-rich manganese-based positive electrode material

    CN117199336A

  • Surface-modified lithium-rich manganese-based positive electrode material with multi-layer core-shell structure and preparation method of surface-modified lithium-rich manganese-based positive electrode material

    CN118016841A

  • Multi-element interface-stable high-voltage all-solid-state battery positive electrode material, preparation method and electrochemical device

    CN119153654A

  • Composite lithium replenishment material, preparation method therefor, and use thereof

    WO2024183705A1